AN INVESTIGATION OF THE CAUSATIVE FACTORS UNDERPINNING STUDENTS' LOW ACADEMIC AND CAREER INTEREST IN CERAMICS IN THE KUMASI METROPOLIS - Jerry Nuako, James; Kwabena Agyei, Isaac; Sam Addo-Danquah, Lord; Adu-Agyem, Joe; Adjei, Kofi (Penerbit Lafadz Jaya, 2023)
Type the English abstract here. Fill abstract or abstract using Times New Roman 11. Abstract The study investigated the causative factors that underpin students' low academic and career interest in ceramics in the Kumasi Metropolis. Three schools made up of one mixed-gender, one all-boys and one all-girls were selected for this study. The study adopted the mixed-methods approach of QUAN+Qual to carry out with its enquiries. Concurrent triangulation of data using questionnaires, interviews, and observation were employed. Participants in the study totaled 273, which consisted of 217 students, 45 teachers, 2 school heads and 9 parents. Four Likert scale-type questionnaires were designed to collect data from the students and teachers. Also, structured interview sessions were held for the school heads and the parents. Frequency and percentage were employed as descriptive statistical tools for analyzing the data collected from the questionnaire and interviews. SPSS v24 and excel spread sheet application facilitated the analysis. The result of the study showed that the Ceramics programme is less prioritized in the majority of the senior high schools, as it was discovered from the investigation that only one of the three schools had a studio facility to enhance teaching and learning. Meanwhile, the study found that the perceptions that there is a low employment opportunity in Ceramics as well as Ceramics being a subject for the low intelligent student were seen as contributing factors to students’ low interest in Ceramics. The study also found that other factors such as scarcity of ceramics text books, the difficulty in obtaining clay for practical activities etc